SYSTEMATIC LITERATURE REVIEW: THE IMPACT OF CHATBOT USE AND SERVICE QUALITY ON CUSTOMER LOYALTY - Octaviyani, Prisella Putri; Sutianingsih, Sutianingsih; Irawan, Nico (Riset Manajemen dan Akuntansi, 2024)
his research examines existing literature to understand how chatbots, as an automationtool in customer service, influence customer perceptions of the quality of service received.Apart from that, this research also assesses how service quality influenced by the use ofchatbots can increase or decrease customer loyalty. The methods used in this literaturereview include analysis of various empirical and theoretical studies that have been published in the fields of customer service technology and customer relationshipmanagement. The review results show that the effective use of chatbots can increaseefficiency and customer satisfaction, which in turn contributes positively to customerloyalty. However, several challenges must be overcome to ensure chatbots can providehigh-quality service.